2016
DOI: 10.1093/rheumatology/kew240
|View full text |Cite
|
Sign up to set email alerts
|

Influence of triple disease modifying anti-rheumatic drug therapy on carotid artery inflammation in drug-naive patients with recent onset of rheumatoid arthritis

Abstract: (18)F-FDG-PET/CT revealed that drug-naive patients with early RA show carotid artery inflammation that can be efficiently reduced by 1-month DMARD triple therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…[ 18 F] FDG micro-PET is a recently developed in vivo imaging tool for screening anti-inflammatory or anti-RA drugs. It allows the visualization of the metabolic activity in inflamed cells ( Haavisto et al, 2016 ). Therefore, we analyzed the accumulation of [ 18 F] FDG in the ankle and knee joints of CIA mice.…”
Section: Resultsmentioning
confidence: 99%
“…[ 18 F] FDG micro-PET is a recently developed in vivo imaging tool for screening anti-inflammatory or anti-RA drugs. It allows the visualization of the metabolic activity in inflamed cells ( Haavisto et al, 2016 ). Therefore, we analyzed the accumulation of [ 18 F] FDG in the ankle and knee joints of CIA mice.…”
Section: Resultsmentioning
confidence: 99%
“…In our patients, we found no change in vascular in ammation at week 12 of treatment. Haavisto et al 17 showed a decrease in vascular in ammation after 4 weeks of triple csDMARDs therapy in treatment naïve patients with RA. Interestingly, this difference in results is in spite of similar SUV max values at baseline between both studies.…”
Section: Discussionmentioning
confidence: 98%
“…[27]. These abnormalities were mostly drug-related and reversible after discontinuation of the treatment [8,10]. On renal biopsy, MPA typically presents as a pauci-immune (devoid of immune complexes), necrotizing and crescentic glomerulonephritis -which is why renal MPA often presents as a rapid progressive disease with advanced stage of renal failure [12].…”
Section: Discussionmentioning
confidence: 99%